Controllable synthesis of graphitic C3N4/ultrathin MoS2 nanosheet hybrid nanostructures with enhanced photocatalytic performance. Issue 39 (7th September 2016) - Lu, Xuejun; Jin, Youlai; Zhang, Xinyi; Xu, Guangqing; Wang, Dongmei; Lv, Jun; Zheng, Zhixiang; Wu, Yucheng
Abstract : Graphitic C3 N4 /ultrathin MoS2 (MoS2 /g-C3 N4 ) hybrids were synthesized via a facile bathing and ultrasound method. Abstract : Graphitic C3 N4 /ultrathin MoS2 (MoS2 /g-C3 N4 ) hybrids were synthesized via a facile bathing and ultrasound method. In this process, a well-bonded interface structure was formed between ultrathin MoS2 nanosheets and g-C3 N4 through adjusting the amount of MoS2 in the MoS2 /g-C3 N4 hybrids. The MoS2 /g-C3 N4 hybrids were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy (Raman), transmission electron microscopy (TEM) and UV-vis spectroscopy (UV-vis). The MoS2 /g-C3 N4 photocatalyst showed excellent photocatalytic activity in the photodegradation of organic pollutants. In this work, methyl orange (MO) was used as the simulative pollutant; the highest photodegradation rate (92.4%) was obtained when the amount of MoS2 was 5 wt% in the MoS2 /g-C3 N4 hybrids (0.05-MC), with a kinetic constant of 0.0189 min −1 after being irradiated under visible light for 2 h. Besides, 0.05-MC also showed excellent recyclability and chemical stability, and a photodegradation rate of 79.93% was reached after being reused 10 times. For practical pollutants, the photocatalytic degradation rates of ciprofloxacin (CIP) and tetracycline hydrochloride (TC) have been increased dramatically under the visible light irradiation. The excellent photocatalytic properties of MoS2 /g-C3 N4 hybrids can be ascribed to the enhanced separation rate and accelerated mobility of photogenerated charges through ultrathin MoS2 nanosheets' modification.